Complex internationalisation strategies during crises - Jaklič, Andreja (Teorija in praksa, 2020)
Studies of firm growth and new exporters in this millennium reveal greater complexity and diversification in internationalisation strategies, especially in small and open economies. We examine the export diversification of Slovenian firms during recent crises. First, we analyse the foreign market and product diversification of exporting firms during the Great Recession and, second, changes in export diversification behaviour since the Covid-19 pandemic. Market and product diversification provided a vital source of enterprises growth, value creation and revenue scaling during the great recession. The analysis shows: (1) Exporters with the strongest growth after the global recession demonstrated high export diversification. (2) In the post Covid- 19 period, the majority of firms did not introduce any change in their export behaviour, but invested in digitalisation and automation. (3) The localising of exports, reduction of export markets and shrinking of the exported product portfolio was far more frequent than diversification, which might limit future growth prospects. (4) Firms that used complex diversification reported faster recovery plan. Managing complexity and export diversification thus remain important tools for overcoming crises, but can also be achieved through increased digitalisation
Keywords: Crises; digitalizacija; diverzifikacija izvoza; diverzifikacija trga; Economic policy; Ekonomska politika; Epidemics; Epidemije; Internacionalizacija; Internationalization; izvoz; kompleksne strategije internacionalizacije; Krize; načini vstopa na tuje trge; produktna diverzifikacija; Strategija; Strategy; tuji trgi